A Review of Recent Evaluations of Nursing Homes in the US using Cost-Benefit Analysis - Brent, Robert J. (Medical Research Archives, 2025)
Recently, a Cost-Benefit Analysis (CBA) was carried out to ascertain whether expenditures on nursing homes are socially worthwhile. It has been well-known for a long while that nursing homes had major problems. But it was only newly discovered just how large were the social losses from these facilities. The objective of this review is to report the scale of these losses and to explain in detail how these negative net-benefits were estimated. Cost estimates were obtained from the literature. The benefit methodology involved using changed Quality Adjusted Life Years (QALYs) to quantify the effects of nursing homes, which were then valued by putting a price on the QALYs. The social welfare loss was estimated, based on a large panel data set, to amount to $1.93 trillion. This sum would be saved if people were able to reside outside nursing homes. Two major reasons for the nursing home loss of benefits were giving residents improper medications (like anti-psychotics) and neglecting to provide necessary services (like hearing aids). For those who were unable to live outside a nursing home, this review summarized an extensive report on nursing homes by the National Academies of Sciences, Engineering and Medicine. Seven recommendations for improvement were outlined. One of the suggested interventions was covered in detail. The seven recommendations can be on the agenda for medical researchers to carry out future CBAs targeting nursing home interventions using methods outlined in this review.